Legacy in the making : building a long-term brand to stand out in a short-term world - Miller, Mark, 1972-; Conley, Lucas (McGraw-Hill, 2018)
A book for a different breed of business leader, this guide celebrates an active, dynamic form of modern legacy, seen through the eyes of a select group of extraordinary men and women who are pursuing their enduring ambitions in the age of now. --